Perbedaan Tingkat Pengetahuan Ibu Rumah Tangga Tentang Pemberantasan Sarang Nyamuk Pada Daerah Endemis Dan Non Endemis DBD Di Kecamatan Karanganyar - Wardoyo, Devy Puspo, dr. Iskandar, M.Kes, dr. Anika Candrasari, M.Kes (2016)
Background: Dengue is an infectious disease caused by the dengue virus infected through the bite of Aedes aegypti mosquito. The problem of dengue does not only have impacts on the clinical problem of the infected individual, but also have impacts on the people's social and economical conditions. One of the causes is insufficiency in knowledge and government's socialization about the right ways to do the efforts. Objectives: This research aimed at analyzing whether there is difference in the level of housewives' knowledge on the eradication of mosquito nests in the endemic dengue area and non endemic dengue area in Karanganyar sub-district. Methods: The research design is the analytic observational design with cross sectional analytic approaches. subjects were 100 people in the endemic dengue area and non endemic dengue area in Karanganyar sub-district who already fullfill the inclusion and exclusion criteria. Results: Based on T test it shows the p value is 0,03. The results showed that the housewives' knowledge level on the eradication of mosquito nests was better in the endemic area. Conclusion: Based on the results of the research, it could be obtained that the housewives' knowledge level on the eradication of mosquito nests in the endemic area was higher than the housewives' knowledge level in the non endemic area.